A year with Mama Earth - Grabill, Rebecca; Green, Rebecca 1986- (Eerdmans Books for Young Readers, 2019)
From one September to the next, Mama Earth supplies children and creatures with a feast of sights, scents, and sounds
Keywords: Jahreszeit; Natur; Kind; Nature; Seasons; Bilderbuch